At the bottom of Shakespeare's ocean - Mentz, Steve (Shakespeare now!, 2009)
"We need a poetic history of the ocean, and Shakespeare can help us find one. There's more real salt in the plays than we might expect. Shakespeare's dramatic ocean spans the God-sea of the ancient world and the immense blue vistas that early modern mariners navigated. Throughout his career, from the opening shipwrecks of The Comedy of Errors through The Tempest, Shakespeare's plays figure the ocean as shocking physical reality and mind-twisting symbol of change and instability. To fathom Shakespeare's ocean -- to go down to its bottom -- this book's chapters focus on different things that humans do with and in and near the sea: fathoming, keeping watch, swimming, beachcombing, fishing, and drowning. Mentz also sets Shakespeare's sea-poetry against modern literary sea-scapes, including the vast Pacific of Moby-Dick, the rocky coast of Charles Olson's Maximus Poems, and the lyrical waters of the postcolonial Caribbean. Uncovering the depths of Shakespeare's maritime world, this book draws out the centrality of the sea in our literary culture"--Provided by publisher.